Drowning : the rescue of flight 1421 [large type] - Newman, T. J. (Novelist) (Blackstone Publishing, 2023)
A commercial jetliner crashes into the Pacific Ocean and sinks to the bottom with passengers trapped inside. More than two hundred feet below the surface, engineer Will Kent and his eleven-year-old daughter Shannon are waist-deep in water and fighting for their lives. Their only chance at survival is an elite rescue team on the surface led by professional diver Chris Kent--Shannon's mother and Will's soon-to-be ex-wife--who must work together with Will to find a way to save their daughter and rescue the passengers from the sealed airplane, teetering on the edge of an undersea cliff.